The Effect of Code-Switching on Iranian Elementary EFL Learners’ Oral Fluency, Accuracy, and Willingness to Communicate - Saeid Noorbar; Homa Jafarpour Mamaghani (Journal of Modern Research in English Language Studies)
Regarding the issue of whether or not the use of L2 learners’ mother tongue should be allowed in the classroom, there has been a discord among scholars, each giving reasons for their claim. Considering this lack of consensus, this study was an attempt to investigate the effect of code-switching (CS) on Iranian elementary English as a Foreign Language (EFL) learners’ oral fluency, accuracy, and willingness to communicate (WTC). To carry out this study, a sample of 60 high-elementary level EFL learners was chosen to take part. After a Key English Test (KET) was administered to ensure homogeneity of the learners, they were divided into two groups of experimental and control. The study used a quasi-experimental design. The instruments used to obtain the needed data were a WTC questionnaire providing quantifiable data on learners’ WTC both inside and outside the classroom, and the speaking section of a KET as pre-test and post-test to see whether the learners’ oral fluency and accuracy changed significantly over the course of the treatment. The results of a Multivariate Analysis of Covariance (MANCOVA) statistical analysis revealed positive effect of CS on the participants’ WTC and oral accuracy and fluency. The results of the present study can contribute to the field of English Language Teaching (ELT) and be of use for practitioners and material developers.